Human gamete micromanipulation and intracytoplasmic sperm injection (ICI) : its impact on severe male infertility - Windt, Marie-Lena (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch Uni versity, 2000.